Dināṅka ke binā - Ḵẖāna, Uṣākiraṇa (Vāṇī Prakāśana, 2022)
Autobiography of a Hindi and Maithili author.
Keywords: Autobiografie; Khāna; Ushākiraṇa; Khāna; Ushākiraṇa; 1945-; Authors; Hindi; 20th century; Biography.; Authors; Maithili; 20th century; Biography.; Authors; Hindi; Authors; Maithili; Biographies